NO DRAMA: ANALISIS KEMAMPUAN REGULASI EMOSI SISWA KELAS XII DALAM MENGHADAPI TEKANAN INTERPERSONAL DARI GURU DAN ORANG TUA - Yeni Pita Sari; Khoirunnisya Dalimunthe; Nanda Yustina (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2026)
Twelfth-grade students face double pressure between academic expectations and interpersonal dynamics with authority figures. This study aims to analyze the emotional regulation abilities of twelfth-grade students in dealing with interpersonal pressure in the form of reprimands or anger from teachers and parents. This study uses a correlational quantitative approach and involves 110 students as respondents selected through simple random sampling. Data were collected using a Likert scale questionnaire that measured aspects of stress control and emotional regulation strategies. The results showed that the majority of students were in the neutral category (39.1%), while another 39.1% showed positive emotional regulation abilities (agreed and strongly agreed to remain calm), and the remaining 21.9% were identified as vulnerable to stress. These findings reveal that although most students are beginning to achieve late adolescent emotional maturity, most others still have fluctuating and situational emotional stability. The ability to remain calm (just calm) is greatly influenced by cognitive reappraisal strategies. The conclusion of this study emphasizes the importance of strengthening emotional literacy and conseling services to help students manage interpersonal pressure without destructive reactions. Assertive communication between teachers, parents, and